Aproximación a la comunidad de San Isidoro de León entre 1156 y 1248 (estudio cuantitativo y cualitativo) - Suárez González, Ana (Estudios humanísticos. Geografía, historia y arte, 1992)
The Archive of the monastery of San Isidoro de León provides us with useful sources - manuscripts, documents - to know how its community was made up in the twelfth and thirteenth centuries. Starting from these sources, we can determine exactly the number of canons, their names and responsibilities in the chronological period from 1156 to 1248.